The World Powers and Iran - Keynoush, Banafsheh. author. aut Link
XIII, 196 p. 1 illus.
Keywords: This book reveals the reasons for and ways in which the Islamic Republic of Iran challenged the world powers, through the pursuit of material and ideational goals, to advance a strong nuclear program in the past decade. The book explores Iran’s interactions with the United States of America, the Russian Federation, the People’s Republic of China, the United Kingdom of Great Britain and Northern Ireland, the French Republic, the Federal Republic of Germany, and the Republic of India, in the period before (2011-2012), during (2013-2016) and after (2017-2021) the finalization of the nuclear deal known as the Joint Comprehensive Plan of Action in 2015. Iran’s narratives and actions to build middle power status are examined at length against the backdrop of its attempts to reshape global politics, the Middle East region, and the future of the nuclear nonproliferation regime. Banafsheh Keynoush is the author of Saudi Arabia and Iran: Friends or Foes? (2016), and the editor of Iran’s Interregional Dynamics in the Near East (2021). She received her PhD from Tufts University, completed coursework at Harvard University, and was a visiting scholar at Princeton University, USA.